2000
DOI: 10.1159/000014270
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Hypoxia-Induced Changes in Newborn Rats

Abstract: In order to investigate the role of nitric oxide (NO) in hypoxic tissue damage in newborns, we studied the effects of systemic administration of an inhibitor of NO synthase, NG-nitro-L-arginine (L-NNA), and the precursor for the synthesis of NO, L-arginine (L-ARG), on the biochemical and histological changes in brain, heart, lung, liver, kidney, intestine, and skeletal muscle tissues. Four groups of 1-day-old Wistar rat pups were used: control, hypoxic, L-ARG, and L-NNA groups. L-ARG 100 mg/kg or L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Differently, Kılıc et al reported that NO effect varied and such effect appeared due to useful hemodynamic effects of NO as well as the balance the cytotoxicity appeared in the kidney and other tissues (40). In the present study, NO enzyme activity was found significantly lower in groups UUO1S, UUO3 and UUO3S than the control group.…”
Section: Conflict Of Interestcontrasting
confidence: 52%
“…Differently, Kılıc et al reported that NO effect varied and such effect appeared due to useful hemodynamic effects of NO as well as the balance the cytotoxicity appeared in the kidney and other tissues (40). In the present study, NO enzyme activity was found significantly lower in groups UUO1S, UUO3 and UUO3S than the control group.…”
Section: Conflict Of Interestcontrasting
confidence: 52%
“…In that regard, a 75% increase in TBARs in rats initially exposed to 12% O 2 for 48 h and to 10% for 12.5 d was found in lung homogenates [183]. Kiliç et al [182] found an increase in TBARs in lung homogenates in newborn rats exposed to 8% O 2 for 3 h. This process was prevented by administering a nitric oxide synthase inhibitor (NG-nitro-L-arginine) and by administering a precursor for its synthesis (L-arginine). Hoshikawa et al [89] found an increase in lipid peroxidation measured as phosphatidylcholine hydroperoxide in lung homogenates after rats were exposed to 10% O 2 for four days.…”
Section: Oxidative Damage In Lungs By Hypoxiamentioning
confidence: 99%
“…NOX inhibitors : diphenyleneiodonium (DPI) [39, 71–73, 91, 207]; peroxisome proliferator-activated receptor (PPAR γ ) [79]; 4-(2-Aminoethyl) benzenesulfonyl fluoride (AEBSF) [74]; apocynin [42, 207]. NOS inhibitors : N G -monomethyl-L-arginine (L-NMMA): inhibitor of the three isoforms [31]; N-(3-(aminomethyl)benzyl) acetamidine (1400 W) and S-methylisothiourea sulfate (SMT): inhibitors of iNOS [31, 59]; L-NG-nitroarginine (L-NNA): inhibitor of eNOS and nNOS [59, 182]. Mitochondrial inhibitors : complex I: rotenone [38, 40]; diphenyleneiodonium (DPI) [39, 71–73, 91], 1-methyl-4-phenylpyridinium (MPP + ) [75].…”
Section: Figurementioning
confidence: 99%
“…In adult animals, administration of L -Arg before an ischemic insult reduces brain infarct area [17][18][19] , increases cerebral blood fl ow [17][18][19][20][21] in parallel to eNO production [1] , and modulates the metabolic derangement in the ischemic brain [20] . In newborn animals, a study with 1-day-old rats shows that L -Arg, administered before a hypoxic insult without ischemia, decreases the rise in lipid peroxidation observed in hypoxic brain [22] . When administered early, benefi cial effects of L -Arg are free of side effects [19][20][21][22][23] , but when administered several hours after a hypoxic-ischemic insult, when iNOS induction has been established, L -Arg increases brain damage [24] .…”
Section: Introductionmentioning
confidence: 99%